Pengaruh Tingkat Konsentrasi Siswa Dan Self Regulated Learning Terhadap Hasil Belajar Ekonomi Siswa Fase F Di SMA Negeri 2 Painan - Sri Nata Zulhen; Caterina Lo; Serli Diovani Teza (Kilau Publishing, 2025)
This study aims to determine the extent to which several factors influence students’ economics learning outcomes in the fifth phase of social studies at SMA Negeri 2 Painan. The objectives include: first, analyzing the effect of student concentration levels on economics learning outcomes; second, examining the influence of self-regulated learning; and third, investigating the simultaneous effect of concentration and self-regulated learning on students’ performance. The research applies a quantitative approach with a population of 70 students in the fifth phase of social studies. Sampling used the saturated sampling technique, ensuring all students were included as respondents. Data were collected through questionnaires and analyzed using multiple linear regression with SPSS version 25. Hypothesis testing was conducted using the t-test for partial influence and the F-test for simultaneous influence. The results demonstrate that student concentration significantly affects economics learning outcomes. This is evidenced by the calculated t-value of 2.700, which is greater than the t-table value of 1.996, with a significance level of 0.009 (<0.05). Likewise, self-regulated learning also shows a significant effect, with a t-value of 2.880 > 1.996 and a significance level of 0.005. Furthermore, concentration and self-regulated learning simultaneously affect learning outcomes, as shown by an F-value of 10.683 > 3.13 and a significance level of 0.000 (<0.05).